Simulation Analysis of a Coandă-Effect Ejector Using CFD - Sierra, Jorge; Ardila, Juan; Vélez, Sebastián; Maya, David; Hincapié, Diego (TECCIENCIA, 2017)
This work presents the optimization of a Coandă-effect air ejector used widely in industry through computational fluid dynamics. This optimization was developed in ANSYS FLUENT® software V16.2. Two 3D models of the commercial ejector (ZH30-X185 by SMC®) were carried out for the simulation procedure, varying the size of the separation of 0.3 and 0.8 mm in the walls of the nozzle, which communicates the high-pressure region and the mixture zone. In the experiment designed, the feed pressure applied to the ejector take values of 0.20, 0.25, and 0.30 MPa and the dynamic fluid behavior was analyzed for the two geometries mentioned. For the numerical and fluid behavior analysis, a mesh study was conducted to guarantee the independence of the results with the number of discretization cells. The k-ε RNG turbulence model was implemented with treatment of walls, solving in stationary manner the phenomenon occurring within it, given that the temporal evolution is quite rapid. Increased secondary mass flow (extracted) relations with respect to the primary mass flow (injected) were found when the separation communicating the high-pressure zone and the mixture zone diminished. With increased feed pressure of the primary flow, a decrease was found in the secondary mass flow relation with respect to the primary mass flow.